2019
DOI: 10.21848/asr.2019.15.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Word Fluency in Healthy Aging and Alzheimer’s Disease

Abstract: Purpose:In general, aging factor or neurological disease degrades a function of working memory, leading poor word fluency. The purpose of this study was to investigate the characteristics of word fluency in healthy aging and Alzheimer's disease (AD). Methods: Nineteen healthy older adults, sixteen mild AD and twelve moderate AD subjects performed semantic and phonemic word fluency tasks. A series of cognitive-linguistic assessments were also administered to index working memory capacity, confrontation naming, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In addition, the correlation between verbal fluency and global coherence revealed that processing speed and inhibition are needed to maintain the theme of discourse as supported by the results of a study that reported that verbal fluency tasks are related to executive functions of processing speed and inhibition (McDowd et al, 2011). Thus, producing a coherent discourse while maintaining a topic and switching between subtopics requires the ability to search for words based on semantic knowledge and to suppress repetitive or irrelevant information that is off topic (Lee and Kim, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the correlation between verbal fluency and global coherence revealed that processing speed and inhibition are needed to maintain the theme of discourse as supported by the results of a study that reported that verbal fluency tasks are related to executive functions of processing speed and inhibition (McDowd et al, 2011). Thus, producing a coherent discourse while maintaining a topic and switching between subtopics requires the ability to search for words based on semantic knowledge and to suppress repetitive or irrelevant information that is off topic (Lee and Kim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between propositional density and verbal fluency indicated that a lower propositional density resulted from a decreased ability to initiate utterances spontaneously, which is associated with processing speed (McDowd et al, 2011), and to maintain the generation of discourse, which is related to inhibitory and switching ability (McDowd et al, 2011; Lee and Kim, 2019). In this study, the aMCI participants also frequently repeated task questions when they began to speak or rephrased predicates during their discourse production due to difficulties in formulating utterances or word retrievals, which lowered their propositional density.…”
Section: Discussionmentioning
confidence: 99%
“…Naming ability is evaluated using confrontation naming and generative naming tests. Among the generative naming parameters, semantic word fluency is related to the function of the temporal lobe, while phonemic word fluency is related to the function of the frontal lobe, which plays a role in lexical-phonemic memory 19 . Therefore, atomoxetine's ability to increase frontal lobe activity may explain improvements in phonemic fluency.…”
Section: Discussionmentioning
confidence: 99%
“…This is because there are deficits in manipulating and processing incoming data. 11,12 Borella et al's study explored WM capacity in individuals aged 20 to 86 years and found that it declines with age. 13 Furthermore, they observed that lower WM capacity is associated with shorter, more straightforward phrases, less complex grammatical structures, and more error word selection and meaning.…”
mentioning
confidence: 99%